The Victim-Offender Overlap Behind Bars: Linking Prison Misconduct and Victimization - Toman, Elisa L. (Justice quarterly, 2019)
Despite a growing body of research on the victim-offender overlap, limited scholarship has examined this phenomenon in the context of the prison. This paper advances theory and scholarship on the victim-offender overlap and prison social order by examining linkages between prison misconduct and victimization. Examination of the overlap in the prison context extends the generality of the model and provides greater insight into the implications of the prison experience on behavior. This paper uses nationally representative data from the Survey of Inmates in State and Federal Correctional Facilities and bi-probit analyses to estimate whether the overlap exists within the prison setting and whether victimization and misconduct can be explained using the same theoretical framework. Findings suggest that common and unique risk factors exist for victimization and misconduct. Results have implications for theory, research, and policy related to understanding the relationship between victims and offenders and deviance in the prison setting.